The learning community for involved learning: Towards cybergogy-based learning - Satria, Dadi; Rasyid, Yulianti; Kristiyani, Ary (Universitas Mulawarman, 2025)
Online learning has significantly transformed education, especially by providing greater flexibility for both students and teachers in learning processes. However, online classes tend to rely more on teacher-centered presentations, allowing them to isolate students from the learning process. The diverse characteristics of students are a challenge for teachers in building interaction and communication and facilitating effective collaboration. A literature review shows that interaction is important for student learning outcomes. Therefore, understanding and categorizing student characteristics is important in building a learning community so that it can improve teacher and student interaction, as outlined in cybergogy-based online learning models. Cybergogy is a new concept of cyber-based learning with three main domains: cognitive, emotional, and social, known as engaged learning. This approach emphasizes the importance of creating a holistic and engaging online learning environment that caters to the diverse needs of learners. The research findings indicate that online learning designed based on cybergogy principles effectively fosters student engagement and collaboration, thereby successfully mitigating key issues that often hinder the effectiveness of online education. By recognizing and addressing the cognitive, emotional, and social aspects of learning, cybergogy aims to foster a sense of community, encourage active participation, and promote deeper understanding.